Solidification Process Investigation of LiCl Salt as PCM with Temperature-Dependent Density and Viscosity by Enthalpy Porosity Simulation Model - Ibrahim, Nur Syah; Luthfie, Alief Avicenna (Journal of Power, Energy, and Control, 2025)
An enthalpy porosity simulation model is widely used to simulate the solidification process of a Phase Change Material (PCM) with constant density and viscosity. Consequently, numerical inaccuracy may arise in the investigation of the solidification process. Therefore, this study investigates the solidification of lithium chloride (LiCl) as a PCM, incorporating temperature-dependent density and viscosity in the enthalpy porosity model. Furthermore, the computational domain is represented by a concentric pipe, with the LiCl salt assumed to be fully filled within the annulus. The boundary conditions are adiabatic on the outer radius and constant temperature on the inner radius, representing the temperature of the Heat Transfer Fluid (HTF). The simulation results show that the solidification process with temperature-dependent density and viscosity required a total time of 2360 s to complete the solidification process. In addition, the solidification rate is decreased at the beginning of the solidification process and then increased before being decreased at the end of the solidification process. Furthermore, a comparison is conducted with constant density and viscosity. The comparison result shows that the solidification time of temperature-dependent density and viscosity is shorter than the solidification process time of constant density and viscosity with a deviation of 8.5%, indicating the importance of using the temperature-dependent density and viscosity to investigate the solidification time. Conversely, the solidification rate shows a similar tendency, indicating the insignificant effect of using the temperature-dependent density and viscosity to investigate the solidification rate.